The measurement of antioxidant capacity and color attributes in wild harvest samphire (Tecticornia sp.) samples using mid‑infrared spectroscopy - Srivarathan, S.; Phan, A.D.T.; Wright, O.; Sultanbawa, Y.; Netzel, M.E.; Cozzolino, D. (University of Jaffna, 2021)
Samphire (Tecticornia sp.) is an underutilized Australian indigenous edible halophyte and has been used as complementary vegetable, salads or salt substitute. The present study aimed to characterize as well as to differentiate wild harvested samphire samples from different sub-locations in the Kimberly Region of Western Australia using mid-infrared spectroscopy. Antioxidant capacity measured as total phenolic content (TPC) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity, and color attributes were determined in the harvested samples using routine reference methods. This data was used to develop mid-infrared calibration models using partial least squares regression. The present study shows the ability of mid-infrared spectroscopy to predict TPC and DPPH radical scavenging capacity in wild harvested samphire samples.
Keywords: Tecticornia; Wild harvest; Infrared; Antioxidant capacity; Color; Quality